Food Fraud as a Global Problem (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
With the development of a globalized food market, food fraud has become a crucial issue around the world. Adulteration, substitution, and the deliberately incorrect labeling of species and the geographical origins of food are considered the main cases of food fraud. Some unscrupulous traders replace special local products with inferior or counterfeit products, substitute labeled food species with others, or extend the shelf life of food by using banned chemicals for economic profit, which can pose a significant threat to human health.Therefore, advanced analytical tools are needed as scientific support against food fraud. Food authentication involves procedures to determine whether the product complies with its labeling and whether it conforms to the legal standards and regulations that govern its consumption. The combination of appropriate techniques and statistical methods is considered a powerful tool for identifying cases of food fraud.This reprint brings together the most recent research advances associated with the latest techniques and methods for identifying food fraud. We hope it will provide references for readers who work, study, or focus on food fraud issues.